1989
DOI: 10.1111/j.1151-2916.1989.tb06269.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Mullite–Silicon Carbide Composites

Abstract: Mullite‐SiC‐whisker composites were prepared by powder processing using two commercial SiC whiskers. These composites were prepared by sintering rather than hot‐pressing. A mulliteSlC‐powder composite and a base line mallite material were also prepared for comparison with the two whisker composite materials. Fracture toughness measurements showed significant enhancement in only one of the whisker composite materials. The microstructure of the four materials was examined by scanning electron microscopy and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Previous studies have reported that partially stabilized zirconia (PSZ) and silicon carbide (SiC) effectively improved the mechanical properties of mullite-matrix composites. [1][2][3][4] However, the oxidation of the SiC constituent would deteriorate the mechanical properties of such composites under high-temperature oxidizing environments. Moreover, the oxidation resistance of SiC-reinforced ceramic-matrix composites could be seriously degraded because of the incorporation of PSZ into the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that partially stabilized zirconia (PSZ) and silicon carbide (SiC) effectively improved the mechanical properties of mullite-matrix composites. [1][2][3][4] However, the oxidation of the SiC constituent would deteriorate the mechanical properties of such composites under high-temperature oxidizing environments. Moreover, the oxidation resistance of SiC-reinforced ceramic-matrix composites could be seriously degraded because of the incorporation of PSZ into the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…S TRUCTURAL type materials such as SiC-whisker-reinforced mullite composites have been studied for many years for their potential use in high-temperature applications. [1][2][3][4][5][6] Hence their mechanical properties 2,5 as well as their thermal properties [7][8][9] have been well characterized. This is not the case with their electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…C ERAMIC-MATRIX composites toughened by SiC whiskers are possible candidates for use in high-temperature environments. [1][2][3][4][5][6][7] Thus, the oxidation behavior of these composites at high temperatures is of great concern. 8 -17 Previous studies 6 -9,14,15 have indicated that the oxidation behavior and mechanical properties of SiC-whisker or particulate-reinforced ceramic-matrix composites are strongly affected by the reaction between the oxidation product (i.e., SiO 2 ) and the matrix.…”
Section: Introductionmentioning
confidence: 99%